Kepastian Hukum Hak Atas Tanah Bagi Warga Baru Di Lokasi Perumahan Resettlemen Kelurahan Naiboanat Kecamatan Kupang Timur Kabupaten Kupang - Vinsensius Tamelab; Maria Viviana Ero Payon; Benediktus Peter Lay (Pusat Riset dan Inovasi Nasional, 2023)
For life man , land have very important role Because in reality will relate forever between man with ground . From aspect social , land No only function as source livelihood for inhabitant society , however also works as place stay or place reside . Problems that arise is , until moment This Still Lots inhabitant society that hasn't get guarantee certainty law right on land , in particular inhabitant new former East Timor. Government action post conflict ask opinion 1999, is with programa settlement return (resettlement). But this program felt Not yet Enough answer problem inhabitant new . why ? Because it's needed public No only question place stay , however more from That is certainty hukm right on their land _ occupy . Because That Country with authority , has responsibility For provide , regulate , protect , as well as ensure certainty law to its citizens , in order for rights on land Can fulfilled or not violated . Mandate enacted constitution _ in Article 33 paragraph 3 and the Law Main points Agrarian No. 5 Year 1960 to be instrument law for the State ( Government ) to ensure well-being for all Indonesian people.